Ethnic disparities in receiving benefits for disability following postpartum mental illness during first two years after delivery: an Israeli nationwide study - Bella Savitsky; Irina Radomislensky; Zhanna Frid; Natalia Gitelson; Saralee Glasser; Tova Hendel (BMC, 2020)
Abstract Background Despite relatively high rates of Postpartum Depression (PPD), little is known about the granting of social security benefits to women who are disabled as a result of PPD or of other postpartum mood and anxiety disorders (PMAD). This study aims to identify populations at risk for underutilization of social security benefits due to PMAD among Israeli women, with a focus on ethnic minorities. Methods This retrospective cohort study is based on the National Insurance Institute (NII) database. The study population included a simple 10% random sample of 79,391 female Israeli citizens who gave birth during 2008-2016 (these women delivered a total of 143,871 infants during the study period), and who had not been eligible for NII mental health disability benefits before 2008. The dependent variable was receipt of Benefit Entitlement (BE) due to mental illness within 2 years following childbirth. Maternal age at delivery, population group, Socio-Economic Status (SES), family status, employment status of the mother and her spouse, and infant mortality were the independent variables. Left truncation COX proportional hazard model with time-dependent variables was used, and birth number served as a time discrete variable. Results Bedouin and Arab women had significantly lower likelihood of BE (2.6 times lower and twice lower) compared with other ethnic groups (HR = 0.38; 95% CI: 0.26-0.56; HR = 0.47; 95% CI: 0.37-0.60 respectively). The probability of divorced or widowed women for BE was significantly higher compared to those living with a spouse (HR = 3.64; 95% CI: 2.49-5.33). Lack of employment was associated with higher likelihood of BE (HR = 1.54; 95% CI: 1.30-1.82). Income had a dose-response relationship with BE in multivariable analysis: lower income was associated with the nearly four-fold greater probability compared to the highest income quartile (HR = 3.83; 95% CI: 2.89-5.07). Conclusions Despite the exceptionally high prevalence of PMAD among ethnic minorities, Bedouins and Arabs had lowest likelihood of Benefit Entitlement. In addition to developing programs for early identification of postpartum emotional disorders among unprivileged ethnic groups, awareness regarding entitlement to a mental health disability allowance among ethnic minorities should be improved.